2022
DOI: 10.30574/gscbps.2022.18.3.0103
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and toxicity study of the aqueous extract of the leaves of Vernonia colorata (Willd.) Drake in Wistar rats

Abstract: The aim of the work is to study phytochemical composition and acute and subacute toxicities of the aqueous extract of leaves of Vernonia colorata (AEVC). The acute toxicity study was performed by administering a single oral dose of AEVC of 5000 mg/kg body weight (bw) to female Wistar rats. For toxicity study, the treatments were administered orally for 28 consecutive days. The control group received distilled water (10 mg/kg bw). The test groups received doses of 100, 500 and 1000 mg/kg bw respectively and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similarly, Ogheneochuko et al [17] found no flavonoids or steroids in A. cordifolia extracts. Also, the presence of polyphenols, tannins and saponosides in aqueous extracts of V. colorata leaves was confirmed by the work of Sawadogo et al [18] with the exception of alkaloids. The presence of polyphenols, flavonoids, tannins, alkaloids, saponins as well as sterols and terpenes in O. gratissimum extracts is confirmed by the results of Kpètèhoto et al [19] with the exception of leucoanthocyanins, as well as those obtained by N'Guessan et al [20] with the absence of saponins.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly, Ogheneochuko et al [17] found no flavonoids or steroids in A. cordifolia extracts. Also, the presence of polyphenols, tannins and saponosides in aqueous extracts of V. colorata leaves was confirmed by the work of Sawadogo et al [18] with the exception of alkaloids. The presence of polyphenols, flavonoids, tannins, alkaloids, saponins as well as sterols and terpenes in O. gratissimum extracts is confirmed by the results of Kpètèhoto et al [19] with the exception of leucoanthocyanins, as well as those obtained by N'Guessan et al [20] with the absence of saponins.…”
Section: Discussionmentioning
confidence: 61%
“…Bonsou et al [55] showed that the fruit of Tetrapleura tetraptera was safe at a single dose of 5000mg/kg body weight. Also, according to the results of Sawadogo et al [18] oral administration of V. colorata at a dose of 5000 mg/kg body weight does not expose the consumer to toxicity risks. According to OECD guideline 423 for chemical testing, the leaf and fruit extracts studied have a lethal dose (LD50) greater than 5000 mg/kg CP [56].…”
Section: Discussionmentioning
confidence: 98%